Analysis of an Inertial Reference System - Monroy, Oscar (2018)
The idea of the open universe is developed in with the purpose of deciphering the mystery of the inertial reference system. It follows that a rst approximation to an inertial reference system would be the center of a four-dimensional sphere. The objective interpretation of the experiments of the mirror inversion and the spin of the electron requires considering an axis of rotation located in an extra spatial dimension, associated with each natural self-organized and autonomous system of three-dimensional space. In addition, it is deduced that the observable universe could be conceived as a dual system, with two opposite symmetrical complementary surfaces which would form a single entity. If one of the surfaces corresponds to the conscious mind of the observer, the other surface must correspond to the unconscious mind of the observer. Reinterpreting the hypersphere concept and introducing the concept of complementary spatial dimensions, diagrams are constructed to show that the observable universe is an open and dynamic system